A organização dos institutos federais de educação, ciência e tecnologia no conjunto da educação profissional brasileira - Monica Maria Teixeira Amorim (2013)
Vocational Education in Brazil, in the current historical context, records a new scenario, based on expansion and redevelopment policies for this teaching modality. The reordering policy of federal vocational education, through organizing the Federal Education, Science and Technology Institutes, or simply Federal Institutes (IF), is a major initiative of Lula's government for Vocational Education, that is resumed under the administration of Dilma Rousseff. The Federal Institutes are multicampiinstitutions of higher, basic, and vocational education, for the provision of vocational and technological education within the multiple types of teaching. They were organized as from the integration of two or more federal institutions of vocational education from a same state, and by the transformation of the Federal Centers for Technological Education and Federal Technical Schools linked to Federal Universities. Today, there are 38 Federal Institutes in all Brazilian states, five of them in Minas Gerais. The present study aimed to analyze the process of organizing this"new" institutionalism. The incipience of studies on the subject and the importance credited to professional education, by current Brazilian educational policies justify the relevance of this study. The research process was structured in three levels, namely: literature review, document analysis, and field research. The field research was conducted in seven (07) out of the ten (10) federal institutions of professional education of Minas Gerais, by the application of electronic questionnaires and interviews with managers of these institutions. The study indicates that the current policy for organizing the Federal Institutes in Brazil, in addition to the proposal to extend the supply of middle level vocational education, represents the consolidation of a school system designed specifically to vocational education and organized along with a secondary and academic type of school.